PERAN GREEN ACCOUNTING DALAM MEMODERASI FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN SUSTAINABILITY REPORT - Heliani; Syakiran, Asqi; Hermawan, Irwan (Jurnal Liabilitas, 2025)
The aim of this research is to determine the effect of profitability, liquidity, company size and leverage on sustainability reports with green accounting as a moderating variable in mining companies listed on the BEI for the 2018-2022 period. This research used a purposive sampling method with certain criteria. Meanwhile, the analysis method to determine the effect of green accounting as a moderating variable between profitability, liquidity, company size and leverage uses the moderated regression analysis (MRA) test. The results of this research show that partially profitability, liquidity and leverage have no effect on sustainability report disclosure. Company size has a significant positive effect on sustainability report disclosure and green accounting cannot moderate the influence of profitability, liquidity, company size and leverage on sustainability report disclosure.